Relationship Between Entrepreneurial Orientation and Personal Characteristics: A Case Study at Pamukkale University, Turkey - Mert, Metin; Barutçu, Esin; Mert, Esvet (European Scientific Journal, ESJ, 2017)
Entrepreneurship is one of the basic dynamics of economic development and increasing the level of social welfare. Especially, entrepreneurship is considered as one of the most important factors determining the economic development and emerges from the transition from industrial society to the information society. The spirit of entrepreneurship usually fosters among people with innate personality traits and is then complemented by environmental influences. The people, who make careers, are aware of their talents especially recognize them during the university age. People are able to set clear goals when making plans for their future. Those with higher entrepreneurial tendency are able to pass on their dreams of new business ideas and step up their own companies. The person who takes the risk and capable of making innovation is called the entrepreneur. Entrepreneurship is a concept ascribed to entrepreneurs who take risks, monitor opportunities, pass them on and make innovation. The purpose of the study, conducted at the Pamukkale University Faculty of Economics and Administrative Sciences, is to determine the entrepreneurship tendencies of the students with different personality traits. A positive relationship was found between personality traits and entrepreneurship tendency as a result of the study.